STUDY OF THE UTILIZATION OF FACILITIES FOR FISH AUCTIONS IN KARAN AUR VILLAGE PARIAMAN TENGAH SUBDISTRICT PARIAMAN CITY SUMATERA BARAT PROVINCE - Yulyana Yulyana; Jonny Zain; Alit Hindri Yani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT A series of research activities using the survey method were carried out to obtain information about the type, existence and capacity of the Fish Auction place (TPI)facilities in Karan Aur sub-district, Pariaman Tengah city, Sumatera Barat Province. All information is useful to find out the conditions, activities and utilization of facilities at TPI Karan Aur. From technical calculations, the ulilization rate of the port pool is 70%, the shipping channel width is 93,75%, the pier is 22,32%, the fuel tank is 96,25% and the ice factory is 60%.Keywords:TPI Karan Aur, Facility, study of utilization of facility